Religious-Ethical Perspectives on Traditional Health Law: Toward Culturally Sensitive Regulation (Contrarius Series: Law & Social Justice, 2026)
Indonesia's rich natural resources and cultural traditions have given rise to a variety of traditional healing practices based on local wisdom passed down through generations. However, amidst the development of modern medicine, legal regulations regarding traditional health still face challenges in balancing medical effectiveness with the cultural, ethical, and religious values of the community. This study aims to examine the religious and ethical perspectives in the formation of traditional health laws in Indonesia and to formulate directions for the development of culturally sensitive regulations. The research method used is normative legal research with a legislative approach, and conceptual research using primary and secondary legal materials analyzed descriptively qualitatively. The results show that traditional health practices in Indonesia function not only as physical therapy but also have a spiritual dimension that strengthens the balance between body, soul, and faith. From an ethical perspective, legal regulations must guarantee patient protection, honesty, responsibility, and respect for the community's cultural autonomy. The integration of religious and ethical values in traditional health regulations has been shown to increase social legitimacy, legal compliance, and social justice. Therefore, the direction of the development of traditional health law in the future needs to be directed towards a legal system that is adaptive, inclusive, and rooted in the cultural and spiritual values of the Indonesian people, without neglecting the principles of medical safety and accountability.